"Accommodating" smoke-free policies: tobacco industry's Courtesy of Choice programme in Latin America. Issue 5 (26th September 2007) - Sebrié, Ernesto M; Glantz, Stanton A
Abstract : Objective: To understand the implementation and effects of the Courtesy of Choice programme designed to "accommodate" smokers as an alternative to smoke-free polices developed by Philip Morris International (PMI) and supported by RJ Reynolds (RJR) and British American Tobacco (BAT) since the mid-1990s in Latin America. Methods: Analysis of internal tobacco industry documents, BAT "social reports", news reports and tobacco control legislation. Results: Since the mid-1990s, PMI, BAT and RJR promoted Accommodation Programs to maintain the social acceptability of smoking. As in other parts of the world, multinational tobacco companies partnered with third party allies from the hospitality industry in Latin America. The campaign was extended from the hospitality industry (bars, restaurants and hotels) to other venues such as workplaces and airport lounges. A local public relations agency, as well as a network of engineers and other experts in ventilation systems, was hired to promote the tobacco industry's programme. The most important outcome of these campaigns in several countries was the prevention of meaningful smoke-free policies, both in public places and in workplaces. Conclusions: Courtesy of Choice remains an effective public relations campaign to undermine smoke-free policies in Latin America. The tobacco companies' accommodation campaign undermines the implementation of measures to protect people from second-hand smoke called for by the World Health Organization Framework Convention on Tobacco Control, perpetuating the exposure to tobacco smoke in indoor enclosed environments.